Impact of COVID-19 Pandemic on Pregnant Mothers - Kapali, Gayetri Darshandhari; Koirala, Manisa; Katuwal, Neeta; Thapa, Sangita; Adhikari, Anuradha; Gachhadar, Rashmi; Neupane, Sharmila; Panta, Ganga (Journal of Institute of Medicine Nepal, 2022)
ntroduction The COVID pandemic has detrimental impact on physical and psychological wellbeing of expectant mothers. Fear and worry during pregnancy amplifies risks and can have negative physical and psychological consequences for mother and newborn outcomes. So this study intended to assess the impact of COVID-19 pandemic on pregnant mothers during pregnancy. Methods Descriptive cross-sectional study design was applied among 123 pregnant mothers who visited antenatal OPD of Tribhuvan University Teaching Hospital. Data were collected through non-probability purposive sampling technique by using interview schedule. Descriptive statistic and inferential statistics were used to analyze the collected data. Results Pregnant mothers faced difficulties to maintain physical wellbeing, 84 (68.3%) did not perform any physical exercise, 96 (78%) were physically inactive, 107(87%) stated absence of sound sleep during pregnancy. Majority i.e. 111 (90.2%) of pregnant mothers perceived fear on outcome of newborn. Likewise, 11(8.9%) had severe impact on their psychological wellbeing during COVID-19 pandemic. Place of residence, number of children and trimester of pregnancy were found to be the strong predictors of psychological impact among pregnant women. Conclusion The impact was seen on exercise, sleep, physical wellbeing whereas pregnant mothers seemed more attentive on healthy diet. They expressed more fear on obstetric or newborn outcome and uncertainty on mode of delivery with this panic situation.